Contrasting responses of plant herbivory and disease to local and landscape drivers - Lu, Yawen; Zheng, Shilu; Tomlinson, Kyle W.; Liu, Jiajia (Plant and soil, 2024)
Aim Plant herbivory and disease, which are often associated with each other but subject to different processes, are pivotal in biodiversity maintenance and ecosystem function. Although drivers of plant herbivory and disease have been widely studied separately, their relationships, patterns and determinants remain unclear in fragmented landscapes. Methods We surveyed incidence and severity of foliar herbivory and disease of 2,027 adult trees within 30 sites in 17 tropical forest fragments in Xishuangbanna, southwestern China. We aim to explore the relationship of plant herbivory and disease, and effects of local environmental variables (forest type, plant richness, elevation, slope, soil properties) and landscape environmental variables (patch size, edge distance, isolation). Results We found that incidence, but not severity of disease was positively correlated with that of herbivory. Herbivory severity and incidence were more associated with local variables; both increased with plant richness but decreased with soil nutrients and pH. In contrast, the landscape variable isolation was the dominant driver of disease, with lower severity and incidence in contiguous forests than forest fragments. Conclusion In summary, we show that herbivory and disease are associated with drivers at different scales in fragmented landscapes. Herbivory is mainly driven by local-scale variables, while disease is mainly driven by landscape-scale variables. To control plant herbivory and disease in fragmented landscapes, increasing landscape connectivity and conserving different forest types are urgently required to maintain ecosystem functions under global land use change.